School meals do not have a given place in Swedish school's quality management. (December 2016) - Olsson, Cecilia; Waling, Maria
Objectives: Sweden is one of three countries worldwide which has a legal requirement to ensure that pupils in compulsory school should be offered free, nutritious school meals. Furthermore, the law states that school meal provision should be included in schools' internal quality management (IQM) system. The objective of this study was to examine to what extent schools in Sweden are following the legal requirement to include school meals in IQM and the relationship between this inclusion and the application of government advisory guidelines regarding school meals. Design: Cross-sectional study. Setting: Head teachers evenly distributed across all regions in Sweden representing municipality schools, independent schools and Sami schools. Method: Web-based questionnaire completed by 216 head teachers. Results: About half of the schools did not meet the legal requirement to include schools meals in the IQM. Furthermore, familiarity with and use of the National Food Agency (NFA) guidelines and the web-based tool School Food Sweden, as well as activities considered as part of a pedagogical school meal and the inclusion of school meals in interdisciplinary work, were reported to be less common in schools not including school meals in their IQM system. Conclusion: Findings suggest that when there is inclusion of school meals in a school's quality management system, the school is also more likely to include school meals as part of educational activities. By acknowledging school meal provision as part of the educational process, possibilities are opened up for health-promoting activities to prevent non-communicable disease.